A cross-institutional investigation of a flipped module on preservice teachers' interest in teaching computational thinking. Issue 1 (2nd January 2020) - Zha, Shenghua; Jin, Yi; Moore, Pamela; Gaston, Joe
Abstract: Informed by the person–object theory of interest, this study deployed a mixed-method concurrent triangulation design and investigated the impact of major/specialization, gender, and module design on preservice teachers' interest in teaching computational thinking. The study was conducted in a flipped computational thinking module hosted in three sections of educational technology courses at two U.S. institutions. Results from the quantitative analysis showed that preservice teachers who did both Scratch coding and physical computing practices had a higher level of interest than their peers who only did the Scratch coding only. Our qualitative analysis found evidence that preservice teachers' interest differed by their gender and major/specialization statuses. At the end, we provided suggestions for future research and practice for teaching computational thinking in teacher education.